Herbal Medicine for Traumatic Brain Injury: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Limitations - Lee, Boram; Leem, Jungtae; Kim, Hyunho; Jo, Hee-Geun; Kwon, Chan-Young (Frontiers in Neurology, 2020)
Background: This systematic review aimed to evaluate the effectiveness (functional outcomes and clinical symptoms) and safety (incidence of adverse events) of herbal medicine (HM) as monotherapy or adjunctive therapy to conventional treatment (CT) for traumatic brain injury (TBI). Methods: We comprehensively searched 14 databases from their inception until July 2019. Randomized controlled trials (RCTs) using HM as monotherapy or adjunctive therapy to treat TBI patients were included. The primary outcomes were functional outcomes, consciousness state, morbidity, and mortality. Meta-analysis was performed to calculate a risk ratio (RR) or mean difference (MD) with 95% confidence intervals (CIs). Methodological quality of RCTs and the strength of evidence were assessed. Results: Thirty-seven RCTs with 3,374 participants were included. According to meta-analysis, HM as a monotherapy (RR 1.29, 95% CI 1.21 to 1.37) or an adjunctive therapy to CT (RR 1.21, 95% CI 1.16 to 1.27) showed significantly better total effective rate based on clinical symptoms, compared to CT alone. Subgroup analysis showed that HM had significantly improved post-concussion syndrome, dizziness, headache, epilepsy, and mild TBI, but not traumatic brain edema, compared to CT. Moreover, HM combined with CT had significantly improved post-concussion syndrome, mental disorder, headache, epilepsy, and mild TBI-like symptoms, but not cognitive dysfunction and posttraumatic hydrocephalus, compared to CT alone. When HM was combined with CT, functional outcomes such as activities of daily living and neurological function were significantly better than in patients treated using CT alone. In terms of the incidence of adverse events, HM did not differ from either CT (RR 0.88, 95% CI 0.33 to 2.30) or placebo (RR 2.29, 95% CI 0.83 to 6.32). However, HM combined with CT showed better safety profile than CT alone (RR 0.64, 95% CI 0.44 to 0.93). Most studies had a high risk of performance bias, and the quality of evidence was mostly rated “very low” to “moderate,” mostly because the included studies had a high risk of bias and imprecise quantitative synthesis results. Conclusion: The current evidence suggests that there is insufficient evidence for recommending HM for TBI in clinical practice. Therefore, further larger, high-quality, rigorous RCTs should be conducted